2017
DOI: 10.3390/toxins9100303
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Nasal Carriage of ST80 and ST152 PVL+ Staphylococcus aureus Isolates from Livestock in Algeria

Abstract: The spread of toxinogenic Staphylococcus aureus is a public health problem in Africa. The objectives of the study were to investigate the rate of S. aureus nasal carriage and molecular characteristics of these strains in livestock and humans in three Algerian provinces. Nasal samples were collected from camels, horses, cattle, sheep and monkeys, as well as humans in contact with them. S. aureus isolates were genotyped using DNA microarray. The rate of S. aureus nasal carriage varied between species: camels (53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 32 publications
12
45
2
1
Order By: Relevance
“…Over the last three years, to the best of our knowledge, only three studies reporting MRSA-ST80 clone have been published. These three articles were published only from North Africa [107,108] and Iran [50]. In general, MRSA infections are declining in certain geographic areas, especially in hospital-associated infections [136,137].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the last three years, to the best of our knowledge, only three studies reporting MRSA-ST80 clone have been published. These three articles were published only from North Africa [107,108] and Iran [50]. In general, MRSA infections are declining in certain geographic areas, especially in hospital-associated infections [136,137].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning animals, Peeters et al reported two strains of MRSA-ST80 PVL+ from nasal swabbing of pigs, in Belgium [106]. In Algeria, Agabou et al reported two ST80 PVL+ isolates from camels and four isolates from sheep between 2015 and 2016 [107]. Mairi et al studied a total of 2130 samples from different ecological niches (animal farms, companion animals, wild animals, food products, and aquatic environment) between January and July 2018.…”
Section: Mrsa-st80 In Extra-human Nichesmentioning
confidence: 99%
See 2 more Smart Citations
“…Было также отмечено, что распространённость LA-MRSA на молочных предприятиях значительно возрастает при наличии свиноферм в радиусе 3 км от них [15]. Устойчивые к метициллину стафилококки были выявлены у верблюдов и овец, однако данные MRSA не родственны CC398 и другим широко распространённым группам LA-MRSA [57].…”
Section: проблема множественной лекарственной устойчивости La-mrsaunclassified